Increased UBE2L6 regulated by type 1 interferon as potential marker in TB. Issue 24 (12th November 2021) - Gao, Jiao; Li, Chonghui; Li, Wenjing; Chen, Haotian; Fu, Yurong; Yi, Zhengjun
Abstract: The aim of this study is to identify potential biomarker of tuberculosis (TB) and determine its function. Differentially expressed mRNAs(DEGs) were selected from a blood database GSE101805, and then, 30 key genes were screened using STING, Cytoscape and further functionally enriched. We then found that only 6 of 13 genes related to ubiquitination (the first in the functional enrichment) were increased significantly. ROC analysis showed that UBE2L6, among 6 genes, had the highest diagnostic value, and then, we found that it also had mild value in differential diagnosis. Moreover, our analysis showed that UBE2L6 may be upregulated by type I interferon, which was further confirmed by us. In addition, we also found that UBE2L6 inhibits the apoptosis of Mycobacterium tuberculosis (Mtb)infected macrophages. Subsequently, we discovered that miR‐146a‐5p, which may target UBE2L6, is reduced in peripheral blood mononuclear cells (PBMC) and plasma of TB, and it also had certain diagnostic efficiency(AUC=0.791). In brief, we demonstrated that UBE2L6 as well as miR‐146a‐5p is a potential biomarker for TB and UBE2L6, which may also plays important role in TB by, at least, modulating Mtb‐infected macrophage apoptosis.